Best Paper Selection (Yearbook of Medical Informatics, 2019)
Eichstaedt JC, Smith RJ, Merchant RM, Ungar LH, Crutchley P, Preotiuc-Pietro D Asch DA, Schwartz HA. Facebook language predicts depression in medical records. Proc Natl Acad Sci U S A 2018;115(44):11203-8 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6217418/Parr SK, Shotwell MS, Jeffery AD, Lasko TA, Matheny ME. Automated mapping of laboratory tests to LOINC codes using noisy labels in a national electronic health record system database. J Am Med Inform Assoc 2018;25(10):1292-300 https://academic.oup.com/jamia/article-abstract/25/10/1292/5075874?redirectedFrom=fulltextXiao C, Ma T, Dieng AB, Blei DM, Wang F. Readmission prediction via deep contextual embedding of clinical concepts. PLoS One 2018;13(4):e0195024 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5890980/